Targeted selective treatment against gastrointestinal nematodes in goats under Mozambican conditions - Edna F.X. Guinda; Sónia M.S. Afonso; Eric R. Morgan; Alsácia Atanásio; Bettencourt P.S. Capece; Jonathan H.I. Tinsley; Jan A. van Wyk; Georg von Samson-Himmelstjerna; Jürgen Krücken (Veterinary Parasitology, 2026)

Are humans cathemeral? The diurnal activity model of Homo sapiens challenged - David R. Samson (Journal of Human Evolution, 2026)

Impacts of large herbivores on savanna plant communities: Predictive models of herbivore selectivity and plant response - Joel O. Abraham; Maria Stahl; Samson Kurukura; Abdikadir Ali Hassan; Jacob R. Goheen; Todd M. Palmer; Tyler R. Kartzinel; Robert M. Pringle (Ecology, 2026)
Large herbivores are among the most ecologically influential and extinction‐prone animals. Megaherbivores, in particular, radically alter vegetation. Yet, few studies have tried to predict the impacts of herbivores—or their extinction—on plant species composition and community structure. First principles suggest that preferred food plants should be most strongly suppressed by herbivores and released by herbivore loss, but this intuition may be misleading if plant responses are strongly contingent on functional traits and/or plant–plant interactions. We sought to predict the responses of plant species to size‐selective herbivore‐exclusion treatments in an African savanna, using data on herbivore diets and plant functional traits. Our analysis had three stages. First, we identified plant traits that predicted selectivity (use relative to availability) by the dominant herbivore species excluded by each experimental treatment: megaherbivores (elephant, giraffe; ≥1000 kg), mesoherbivores (buffalo, zebra, impala; 40–600 kg), and dik‐dik (5 kg). Several plant traits predicted selectivity across multiple herbivore species, but each species' diet was best predicted by a distinctive suite of traits. Second, we tested whether herbivore selectivity alone predicted plant responses. Elephant selectivity uniquely predicted plant responses in exclosures relative to unfenced control plots ( R 2 = 0.24–0.30); plant taxa strongly favored by elephants were ninefold more abundant inside exclosures. However, herbivore selectivity failed to predict differences in community structure between the different fenced exclusion treatments, suggesting that bottom‐up effects of competition may intensify relative to consumptive effects as smaller herbivores are removed. Third, we show that including plant traits as covariates alongside elephant selectivity modestly improved predictability ( R 2 = 0.27–0.50). Despite various sources of uncertainty and imprecision inherent in our approach, we show that elephant foraging decisions are a major determinant of plant community dynamics. Our findings indicate that models based on readily attainable data can substantially predict plant community responses to the loss or reintroduction of megafauna. Future work can refine our approach by incorporating additional plant traits associated with tolerance and competition, along with mechanistic measurements of herbivore preferences and biomass consumption, to predict even more accurately how large‐herbivore population declines and extinctions will impact plant communities.

Development of Indirect Tensile Strength (ITS) model and resilient modulus assessment considering moisture conditions on bituminous mixtures - A. Jegan Bharath Kumar; V. Sunitha; R. T. Arjun Siva Rathan; Samson Mathew (Innovative Infrastructure Solutions, 2026)

Can Instagram contribute to the wellbeing and flourishing of Australian farming women in the midst of climate challenges? - Amy R. Samson; Kelly S. Fielding; Natalie Collie (Journal of Rural Studies, 2025)

P05-02 Impact of sub-chronic dioxin exposure on the cardiorenal syndrome - R. Courcoux; R. Souktani; G. Berge; M. Quétin; M. Le Garff; S. Placier; C. Samson; J. Hadchouel; M. Gervais (Toxicology Letters, 2025)

Molecular barcoding of yellow-lipped sea krait, Laticauda colubrina (Schneider, 1799) from the Andaman Islands, India - Jessica Barman; Samson Rokkarukala; Anwesh Maile; S. Rajendra; R. Mohanraju (Ecological Genetics and Genomics, 2025)

Numerical modeling of clay-rich submarine landslides using a novel material point method coupled with computational fluid dynamics - Erik R Sørlie; Quoc A Tran; Gudmund R Eiksund; Samson A Degago (Landslides, 2025)
Submarine landslides present significant hazards to offshore and nearshore environments. This study presents a novel approach to numerically simulate clay-rich submarine landslide events using a recently developed coupled material point method and computational fluid dynamics (MPM-CFD). The landslide events are modeled from their initiation to deposition. In this method, the soils and bedrock are represented by material point method (MPM), while water and air are modeled by computational fluid dynamics (CFD). The constitutive soil model accounts for both strain softening and strain rate dependency. The method can investigate the interaction with the ambient water, the transition from intact to remolded soils, seabed entrainment, and retrogressive and progressive release mechanisms. This study demonstrated that the MPM-CFD method can successfully replicate submarine slides in both model test experiments and a well-characterized field event. In both cases, the soil parameters are determined from detailed site-specific field and laboratory tests. The numerical simulations successfully replicated the results under both conditions. Consequently, the capability of the model to make class-A predictions makes it as a highly promising framework for predicting future submarine landslide events.

Structured decision-making shows broad support from diverse stakeholders for habitat conservation and restoration in Kenya’s Central Highlands - Gwili E.M. Gibbon; Martin Dallimer; Hassan Golo; Humphrey Munene; Charlene A. Wandera; Monda N. Edson; Jane C. Gachura; Tim Hobbs; Festus Ihwagi; Stephen R. Ikhamati; Samson K. Ikiara; David Kimathi; et al. (Land Use Policy, 2024)

Experimental study on erosion of clays during rapid flows - Erik R. Sørlie; Quoc A. Tran; Gudmund R. Eiksund; Samson A. Degago; Heidi Kjennbakken; Tonni F. Johansen (Ocean Engineering, 2024)

CometChip enables parallel analysis of multiple DNA repair activities [DNA repair 106 (2021) 103176–103202] - Jing Ge; Le P. Ngo; Simran Kaushal; Ian J. Tay; Elina Thadhani; Jennifer E. Kay; Patrizia Mazzucato; Danielle Chow; Jessica Fessler; David M. Weingeist; Robert W. Sobol; Leona D. Samson; et al. (DNA Repair, 2024)

Inter-fractional portability of deep learning models for lung target tracking on cine imaging acquired in MRI-guided radiotherapy - Jiayuan Peng; Hayley B. Stowe; Pamela P. Samson; Clifford G. Robinson; Cui Yang; Weigang Hu; Zhen Zhang; Taeho Kim; Geoffrey D. Hugo; Thomas R. Mazur; Bin Cai (Physical and Engineering Sciences in Medicine, 2024)

Design Charts for Jointed Rock Slopes Susceptible to Slide-Head Toppling Failure - Abdul Samson; Victor Mwango Bowa; Peter R. K. Chileshe; Sydney Chinyanta (Geotechnical and Geological Engineering, 2024)

Atmospheric deposition of microplastics in a rural region of North China Plain - Jingjing Li; Jinrui Zhang; Siyang Ren; Daqi Huang; Fobang Liu; Zhen Li; Hanyue Zhang; Mingyu Zhao; Yuxuan Cao; Samson Mofolo; Jiexi Liang; Wen Xu; et al. (Science of The Total Environment, 2023)

Physical model tests of clay-rich submarine landslides and resulting impact forces on offshore foundations - Erik R. Sørlie; Lukas O. Hartnik; Quoc Anh Tran; Gudmund R. Eiksund; Vikas Thakur; Heidi Kjennbakken; Samson Degago (Ocean Engineering, 2023)

Review of gene drive modelling and implications for risk assessment of gene drive organisms - Johannes L. Frieß; Carina R. Lalyer; Bernd Giese; Samson Simon; Mathias Otto (Ecological Modelling, 2023)

Review of the stability analyses for slide-head toppling failure mechanisms: a different perspective - Abdul Samson; Victor Mwango Bowa; Peter R. K. Chileshe; Sydney Chinyanta (Arabian Journal of Geosciences, 2023)

Ecological consequences of large herbivore exclusion in an A frican savanna: 12 years of data from the UHURU experiment - Jesse M. Alston; Courtney G. Reed; Leo M. Khasoha; Bianca R. P. Brown; Gilbert Busienei; Nathaniel Carlson; Tyler C. Coverdale; Megan Dudenhoeffer; Marissa A. Dyck; John Ekeno; Abdikadir A. Hassan; Rhianna Hohbein; et al. (Ecology, 2022)
Diverse communities of large mammalian herbivores (LMH), once widespread, are now rare. LMH exert strong direct and indirect effects on community structure and ecosystem functions, and measuring these effects is important for testing ecological theory and for understanding past, current, and future environmental change. This in turn requires long‐term experimental manipulations, owing to the slow and often nonlinear responses of populations and assemblages to LMH removal. Moreover, the effects of particular species or body‐size classes within diverse LMH guilds are difficult to pinpoint, and the magnitude and even direction of these effects often depends on environmental context. Since 2008, we have maintained the Ungulate Herbivory Under Rainfall Uncertainty (UHURU) experiment, a series of size‐selective LMH exclosures replicated across a rainfall/productivity gradient in a semiarid Kenyan savanna. The goals of the UHURU experiment are to measure the effects of removing successively smaller size classes of LMH (mimicking the process of size‐biased extirpation) and to establish how these effects are shaped by spatial and temporal variation in rainfall. The UHURU experiment comprises three LMH‐exclusion treatments and an unfenced control, applied to nine randomized blocks of contiguous 1‐ha plots ( n = 36). The fenced treatments are MEGA (exclusion of megaherbivores, elephant and giraffe), MESO (exclusion of herbivores ≥40 kg), and TOTAL (exclusion of herbivores ≥5 kg). Each block is replicated three times at three sites across the 20‐km rainfall gradient, which has fluctuated over the course of the experiment. The first 5 years of data were published previously ( Ecological Archives E095‐064) and have been used in numerous studies. Since that publication, we have (1) continued to collect data following the original protocols, (2) improved the taxonomic resolution and accuracy of plant and small‐mammal identifications, and (3) begun collecting several new data sets. Here, we present updated and extended raw data from the first 12 years of the UHURU experiment (2008–2019). Data include daily rainfall data throughout the experiment; annual surveys of understory plant communities; annual censuses of woody‐plant communities; annual measurements of individually tagged woody plants; monthly monitoring of flowering and fruiting phenology; every‐other‐month small‐mammal mark–recapture data; and quarterly large‐mammal dung surveys. There are no copyright restrictions; notification of when and how data are used is appreciated and users of UHURU data should cite this data paper when using the data.

Functional traits driving species role in the structure of terrestrial vertebrate scavenger networks - Esther Sebastián‐González; Zebensui Morales‐Reyes; Francisco Botella; Lara Naves‐Alegre; Juan M. Pérez‐García; Patricia Mateo‐Tomás; Pedro P. Olea; Marcos Moleón; Jomar Magalhães Barbosa; Fernando Hiraldo; Eneko Arrondo; José A. Donázar; et al. (Ecology, 2021)
Species assemblages often have a non‐random nested organization, which in vertebrate scavenger (carrion‐consuming) assemblages is thought to be driven by facilitation in competitive environments. However, not all scavenger species play the same role in maintaining assemblage structure, as some species are obligate scavengers (i.e., vultures) and others are facultative, scavenging opportunistically. We used a database with 177 vertebrate scavenger species from 53 assemblages in 22 countries across five continents to identify which functional traits of scavenger species are key to maintaining the scavenging network structure. We used network analyses to relate ten traits hypothesized to affect assemblage structure with the “role” of each species in the scavenging assemblage in which it appeared. We characterized the role of a species in terms of both the proportion of monitored carcasses on which that species scavenged, or scavenging breadth (i.e., the species “normalized degree”), and the role of that species in the nested structure of the assemblage (i.e., the species “paired nested degree”), therefore identifying possible facilitative interactions among species. We found that species with high olfactory acuity, social foragers, and obligate scavengers had the widest scavenging breadth. We also found that social foragers had a large paired nested degree in scavenger assemblages, probably because their presence is easier to detect by other species to signal carcass occurrence. Our study highlights differences in the functional roles of scavenger species and can be used to identify key species for targeted conservation to maintain the ecological function of scavenger assemblages.

Gibbon sleep quantified: the influence of lunar phase and meteorological variables on activity in Hylobates moloch and Hylobates pileatus - Kaleigh R. Reyes; Ujas A. Patel; Charles L. Nunn; David R. Samson (Primates, 2021)

Oxide mineralogy and trace element chemistry as an index to magma evolution and Marathon-type mineralization in the Eastern Gabbro of the alkaline Coldwell Complex, Canada - M. J. Brzozowski; I. M. Samson; J. E. Gagnon; D. J. Good; R. L. Linnen (Mineralium Deposita, 2021)

Spatial accessibility analysis of schools using geospatial techniques - R. Shanmathi Rekha; Nisha Radhakrishnan; Samson Mathew (Spatial Information Research, 2020)

Flavonoids against the Warburg phenotype—concepts of predictive, preventive and personalised medicine to cut the Gordian knot of cancer cell metabolism - Marek Samec; Alena Liskova; Lenka Koklesova; Samson Mathews Samuel; Kevin Zhai; Constanze Buhrmann; Elizabeth Varghese; Mariam Abotaleb; Tawar Qaradakhi; Anthony Zulli; Martin Kello; Jan Mojzis; et al. (EPMA Journal, 2020)
The Warburg effect is characterised by increased glucose uptake and lactate secretion in cancer cells resulting from metabolic transformation in tumour tissue. The corresponding molecular pathways switch from oxidative phosphorylation to aerobic glycolysis, due to changes in glucose degradation mechanisms known as the ‘Warburg reprogramming’ of cancer cells. Key glycolytic enzymes, glucose transporters and transcription factors involved in the Warburg transformation are frequently dysregulated during carcinogenesis considered as promising diagnostic and prognostic markers as well as treatment targets. Flavonoids are molecules with pleiotropic activities. The metabolism-regulating anticancer effects of flavonoids are broadly demonstrated in preclinical studies. Flavonoids modulate key pathways involved in the Warburg phenotype including but not limited to PKM2, HK2, GLUT1 and HIF-1. The corresponding molecular mechanisms and clinical relevance of ‘anti-Warburg’ effects of flavonoids are discussed in this review article. The most prominent examples are provided for the potential application of targeted ‘anti-Warburg’ measures in cancer management. Individualised profiling and patient stratification are presented as powerful tools for implementing targeted ‘anti-Warburg’ measures in the context of predictive, preventive and personalised medicine.

Correction to: Chimpanzee (Pan troglodytes schweinfurthii) Group Sleep and Pathogen-Vector Avoidance: Experimental Support for the Encounter-Dilution Effect - David R. Samson; Luke A. Louden; Katie Gerstner; Samantha Wylie; Ben Lake; Bradley J. White; Charles L. Nunn; Kevin D. Hunt (International Journal of Primatology, 2019)

Chimpanzee (Pan troglodytes schweinfurthii) Group Sleep and Pathogen-Vector Avoidance: Experimental Support for the Encounter-Dilution Effect - David R. Samson; Luke A. Louden; Katie Gerstner; Samantha Wylie; Ben Lake; Bradley J. White; Charles L. Nunn; Kevin D. Hunt (International Journal of Primatology, 2019)

Scavenging in the Anthropocene: Human impact drives vertebrate scavenger species richness at a global scale - Esther Sebastián‐González; Jomar Magalhães Barbosa; Juan M. Pérez‐García; Zebensui Morales‐Reyes; Francisco Botella; Pedro P. Olea; Patricia Mateo‐Tomás; Marcos Moleón; Fernando Hiraldo; Eneko Arrondo; José A. Donázar; Ainara Cortés‐Avizanda; et al. (Global Change Biology, 2019)
Understanding the distribution of biodiversity across the Earth is one of the most challenging questions in biology. Much research has been directed at explaining the species latitudinal pattern showing that communities are richer in tropical areas; however, despite decades of research, a general consensus has not yet emerged. In addition, global biodiversity patterns are being rapidly altered by human activities. Here, we aim to describe large‐scale patterns of species richness and diversity in terrestrial vertebrate scavenger (carrion‐consuming) assemblages, which provide key ecosystem functions and services. We used a worldwide dataset comprising 43 sites, where vertebrate scavenger assemblages were identified using 2,485 carcasses monitored between 1991 and 2018. First, we evaluated how scavenger richness (number of species) and diversity (Shannon diversity index) varied among seasons (cold vs. warm, wet vs. dry). Then, we studied the potential effects of human impact and a set of macroecological variables related to climatic conditions on the scavenger assemblages. Vertebrate scavenger richness ranged from species‐poor to species rich assemblages (4–30 species). Both scavenger richness and diversity also showed some seasonal variation. However, in general, climatic variables did not drive latitudinal patterns, as scavenger richness and diversity were not affected by temperature or rainfall. Rainfall seasonality slightly increased the number of species in the community, but its effect was weak. Instead, the human impact index included in our study was the main predictor of scavenger richness. Scavenger assemblages in highly human‐impacted areas sustained the smallest number of scavenger species, suggesting human activity may be overriding other macroecological processes in shaping scavenger communities. Our results highlight the effect of human impact at a global scale. As species‐rich assemblages tend to be more functional, we warn about possible reductions in ecosystem functions and the services provided by scavengers in human‐dominated landscapes in the Anthropocene.

Penicillium hermansii, a new species causing smoky mould in white button mushroom production - J. Houbraken; K. A. Seifert; R. A. Samson (Mycological Progress, 2019)

The assessment of the genotoxicity of e-waste leachates from e-waste dumpsites in Metro Manila, Philippines - Z. F. Alam; A. J. V. Riego; J. H. R. P. Samson; S. A. V. Valdez (International Journal of Environmental Science and Technology, 2019)

Microtubules are reorganised and fragmented for uterine receptivity - Sadaf N. Kalam; Samson Dowland; Laura Lindsay; Christopher R. Murphy (Cell and Tissue Research, 2018)

Towards a realistic simulation of boreal summer tropical rainfall climatology in state-of-the-art coupled models: role of the background snow-free land albedo - P. Terray; K. P. Sooraj; S. Masson; R. P. M. Krishna; G. Samson; A. G. Prajeesh (Climate Dynamics, 2018)

Studying Land Use Travel Demand Interaction Using 3S Technology for Tiruchirappalli City - Nisha Radhakrishnan; R. Aswathy; Samson Mathew (Journal of the Indian Society of Remote Sensing, 2017)

The regional impact of Land-Use Land-cover Change (LULCC) over West Africa from an ensemble of global climate models under the auspices of the WAMME2 project - Aaron Anthony Boone; Yongkang Xue; Fernando De Sales; Ruth E. Comer; Samson Hagos; Sarith Mahanama; Kathleen Schiro; Guoqiong Song; Guiling Wang; S. Li; Carlos R. Mechoso (Climate Dynamics, 2016)

West African monsoon decadal variability and surface-related forcings: second West African Monsoon Modeling and Evaluation Project Experiment (WAMME II) - Yongkang Xue; Fernando De Sales; William K.-M. Lau; Aaron Boone; Kyu-Myong Kim; Carlos R. Mechoso; Guiling Wang; Fred Kucharski; Kathleen Schiro; Masahiro Hosaka; Suosuo Li; Leonard M. Druyan; et al. (Climate Dynamics, 2016)

Biodegradation of pesticides using fungi species found in the aquatic environment - B. R. Oliveira; A. Penetra; V. V. Cardoso; M. J. Benoliel; M. T. Barreto Crespo; R. A. Samson; V. J. Pereira (Environmental Science and Pollution Research, 2015)

PTRF is associated with caveolin 1 at the time of receptivity: but SDPR is absent at the same time - Romanthi J. Madawala; Connie E. Poon; Samson N. Dowland; Christopher R. Murphy (Histochemistry and Cell Biology, 2015)

Performance of Small‐Scale Water Management Interventions on Crop Yield, Water Use and Productivity in Three Agro‐Ecologies of Malawi - Davie M. Kadyampakeni; Samson Kazombo‐Phiri; Bancy Mati; Isaac R. Fandika (Irrigation and Drainage, 2015)
Agricultural water management interventions play a critical role in mitigating hunger during droughts and dry seasons in southern Africa. A study was conducted in Malawi to compare the performance of improved agricultural water management interventions with traditional water management practices to assess the performance of the interventions on crop yield and water use. The study used questionnaires and focused group discussions to collect data from farmers and key informants. The results showed significant gains using regulated surface irrigation compared with unregulated surface irrigation. The results showed that yield increases of 33 and 37% for onion and tomato respectively were obtained from wetland seepage irrigation compared with upland cultivation. Treadle pump irrigation increased crop production by 5–54% compared with water can irrigation. Treadle pumps also increased gross and net incomes by ≥12%, suggesting that farmers using the treadle pump were able to realize higher incomes across all crop enterprises compared with farmers using water cans. However, there is a dire need to improve the efficiency of the surface irrigation systems for rice production because the water applied was about two to three times the gross irrigation requirement which could result in environmental degradation through increased salinity and waterlogging. Copyright © 2014 John Wiley & Sons, Ltd.

Physico-chemical properties of tamarind (Tamarindus indica L.) fruits from Mali: selection of elite trees for domestication - N. Van den Bilcke; K. Alaerts; S. Ghaffaripour; D. J. Simbo; R. Samson (Genetic Resources and Crop Evolution, 2014)

Penicillium subrubescens, a new species efficiently producing inulinase - S. Mansouri; J. Houbraken; R. A. Samson; J. C. Frisvad; M. Christensen; D. E. Tuthill; S. Koutaniemi; A. Hatakka; P. Lankinen (Antonie van Leeuwenhoek, 2013)

Do chimpanzees (Pan troglodytes schweinfurthii) exhibit sleep related behaviors that minimize exposure to parasitic arthropods? A preliminary report on the possible anti-vector function of chimpanzee sleeping platforms - David R. Samson; Michael P. Muehlenbein; Kevin D. Hunt (Primates, 2013)

The chimpanzee nest quantified: morphology and ecology of arboreal sleeping platforms within the dry habitat site of Toro-Semliki Wildlife Reserve, Uganda - David R. Samson (Primates, 2012)

Immunotoxicity of Tannery Effluent to the Freshwater Fish Cyprinous carpio - A. G. Murugesan; A. Ramathilaga; J. K. Samson Ponselvan; R. Dinagaran Michael (Bulletin of Environmental Contamination and Toxicology, 2012)

Comparative study on baobab fruit morphological variation between western and south-eastern Africa: opportunities for domestication - A. Cuni Sanchez; S. De Smedt; N. Haq; R. Samson (Genetic Resources and Crop Evolution, 2011)

Phenotypic variation of baobab (Adansonia digitata L.) fruit traits in Mali - S. De Smedt; K. Alaerts; A. M. Kouyaté; P. Van Damme; G. Potters; R. Samson (Agroforestry Systems, 2011)

Computational models of reinforcement learning: the role of dopamine as a reward signal - R. D. Samson; M. J. Frank; Jean-Marc Fellous (Cognitive Neurodynamics, 2010)

Effect of legume plant density and mixed culture on symbiotic N2 fixation in five cowpea (Vigna unguiculata L. Walp.) genotypes in South Africa - Joachim H. J. R. Makoi; Samson B. M. Chimphango; Felix D. Dakora (Symbiosis, 2009)

Decreased expression of Intestinal I- and L-FABP levels in rare human genetic lipid malabsorption syndromes - S. Guilmeau; I. Niot; J. P. Laigneau; H. Devaud; V. Petit; N. Brousse; R. Bouvier; L. Ferkdadji; C. Besmond; L. P. Aggerbeck; A. Bado; M. E. Samson-Bouma (Histochemistry and Cell Biology, 2007)

Soil sampling for Metarhizium anisopliae spores in Queensland sugarcane fields - Mohamed N. Sallam; Catherine A. McAvoy; Peter R. Samson; Judy J. Bull (BioControl, 2007)

Effect of danofloxacin (Advocin A180) on goats affected with contagious caprine pleuropneumonia - U. Ozdemir; G. R. Loria; K. S. Godinho; R. Samson; T. G. Rowan; C. Churchward; R. D. Ayling; R. A. J. Nicholas (Tropical Animal Health and Production, 2006)

Potential Use of the Plant Antioxidant Network For Environmental Exposure Assessment of Heavy Metals in Soils - E. Meers; A. Ruttens; W. Geebelen; J. Vangronsveld; R. Samson; K. Vanbroekhoven; M. Vandegehuchte; L. Diels; F. M. G. Tack (Environmental Monitoring and Assessment, 2006)

Forest resource assessment in mohand forest range, Uttar Pradesh using remote sensing and GIS - I. J. singh; D. K. Jugran; Samson Thanruma; S. R. Reddy (Journal of the Indian Society of Remote Sensing, 2005)

Species Extinction in the Marine Environment: Tasmania as a Regional Example of Overlooked Losses in Biodiversity - GRAHAM J. EDGAR; CATH R. SAMSON; NEVILLE S. BARRETT (Conservation Biology, 2005)
We used Tasmania as a case example to question the consensus that few marine species have recently become extinct or are approaching extinction. Threats to marine and estuarine species—primarily in the form of climate change, invasive species, fishing, and catchment discharges—are accelerating, fully encompass species ranges, and are of sufficient magnitude to cause extinction. Our ignorance of declining biodiversity in the marine environment largely results from an almost complete lack of systematic broad‐scale sampling and an overreliance on physicochemical data to monitor environmental trends. Population declines for marine species approaching extinction will generally go unnoticed because of the hidden nature of their environment and lack of quantitative data.

Nucleotide sequence of the 5′-terminus of Newcastle disease virus and assembly of the complete genomic sequence: agreement with the “rule of six” - R. J. Phillips; A. C. R. Samson; P. T. Emmerson (Archives of Virology, 1998)

Correction - Sijun Liu; Ian D. Bedford; Peter G. Markham; Morad Ghanim; Muhamad Zeidan; Henryk Czosnek; A. Bruyère; E. Herrbach; V. Brault; V. Ziegler-Graff; H. Guilley; J. F. J. M. Heuvel; et al. (Phytoparasitica, 1998)

Abstracts of presentations on plant protection issues at the xth international congress of virology - Sijun Liu; Ian D. Bedford; Peter G. Markham; Morad Ghanim; Muhamad Zeidan; Henryk Czosnek; A. Bruyère; E. Herrbach; V. Brault; V. Ziegler-Graff; H. Guilley; J. F. J. M. van den Heuvel; et al. (Phytoparasitica, 1998)

Penicillium discolor, a new species from cheese, nuts and vegetables - Jens C. Frisvad; Robert a. Samson; Birgitte R. Rassing; Marjolein I. van der Horst; F.T.J. van Rijn; J. Stark (Antonie van Leeuwenhoek, 1997)

The Newcastle disease virus V protein binds zinc - M. Steward; A. C. R. Samson; W. Errington; P. T. Emmerson (Archives of Virology, 1995)

Detection of potato leafroll virus by visual inspection, direct tissue blotting and ELISA techniques - J. L. Whitworth; R. G. Samson; T. C. Allen; A. R. Mosley (American Journal of Potato Research, 1993)

Sequence analysis of temperature sensitive and ?neuraminidase-tolerant? mutants of Newcastle disease virus (strain Beaudette C) - J. Hughes; K. Yusoff; R. Hardy; H. McCartney; P. T. Emmerson; A. C. R. Samson (Archives of Virology, 1991)

Chemotaxonomy of the genus Talaromyces - J. C. Frisvad; O. Filtenborg; R. A. Samson; A. C. Stolk (Antonie van Leeuwenhoek, 1990)

Preliminary studies on the efficacy and establishment ofRoptrocerus xylophagorum [Hym.: Torymidae], a parasitoid ofIps grandicollis [Col.: Scolytidae], in Australia - P. R. Samson; J. Smibert (BioControl, 1986)

Metals in riparian wildlife of the lead mining district of southeastern Missouri - Kenneth R. Niethammer; Richard D. Atkinson; Thomas S. Baskett; Fred B. Samson (Archives of Environmental Contamination and Toxicology, 1985)

The taxonomic situation in the hyphomycete generaPenicillium, Aspergillus andFusarium - R. A. Samson; W. Gams (Antonie van Leeuwenhoek, 1984)

The biology ofRoptrocerus xylophagorum [Hym.: Torymidae], with a note on its taxonomic status - P. R. Samson (BioControl, 1984)

On the taxonomy of the entomogenous fungus Filobasidiella arachnophila - R. A. Samson; J. A. Stalpers; A. C. M. Weijman (Antonie van Leeuwenhoek, 1983)

Modern aspects of food mycology - R. A. Samson (Antonie van Leeuwenhoek, 1982)

The taxonomy ofPenicillium species from fermented cheeses - R. A. Samson; Christiane Eckardt; R. Orth (Antonie van Leeuwenhoek, 1977)

A taxonomic study of the Penicillium chrysogenum series - R. A. Samson; R. Hadlok; Amelia C. Stolk (Antonie van Leeuwenhoek, 1977)

Additional notes on species ofAspergillus, Eurotium andEmericella from Egyptian desert soil - R. A. Samson; J. Mouchacca (Antonie van Leeuwenhoek, 1975)

Some interesting species of Emericella and Aspergillus from Egyptian desert soil - R. A. Samson; J. Mouchacca (Antonie van Leeuwenhoek, 1974)

Scopulariopsis murina, a new fungus from self-heated compost - R. A. Samson; Agnes Klopotek (Archives of Microbiology, 1972)

The relation of cumulative amount and frequency of rainfall and mean temperature to late blight in Indiana - J. R. Wallin; R. W. Samson (American Journal of Potato Research, 1953)

Influence of time of planting of potatoes in indiana muck soil on yield and scab development - R. W. Samson; N. Kent Ellis (American Journal of Potato Research, 1943)